Menanamkan Karakter Peduli Lingkungan pada Naskah Sandiwara Dhemit Karya Heru Kesawa Murti untuk Pengembangan Materi Ajar Mata Kuliah Kajian dan Apresiasi Drama - Waluyo, Budi; Fitriana, Tya Resta; Veronika, Prima (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2021)
This study aims to describe in-depth the values ​​of character education in the play script Dhemit by Heru Kesawa Murti and to describe the relevance of the play script Dhemit by Heru Kesawa Murti as teaching material in the course of Drama Studies and Appreciation of the Javanese Language Education Study Program. The method used is descriptive qualitative. The object studied is in the form of literary texts, namely the drama script Dhemit by Heru Kesawa Murti. This qualitative descriptive method is used to explore sources of information (data), in the form of literary texts so that the data that appears is in the form of concepts or categories that are impossible to calculate with statistics. The approach used in this research is structural, namely interpreting the deep meaning of the literary works studied in relation to people's lives. The data collection techniques used were: (1) recording documents/archives, (2) listening and note-taking techniques, and (3) library research techniques. The results of the research findings with a structural approach show that: (1) There are character education values ​​in Heru Kesawa Murti's drama script Dhemit (2) The values ​​found in Heru Kesawa Murti's drama Dhemit can be used for developing eye learning materials Drama Study and Appreciation Lecture in the Javanese Language Education Study Program.